Dietary Fat and Protein Intakes in Relation to Plasma Sphingolipids As Determined by a Large-Scale Lipidomic Analysis. (7th June 2021) - Hoong, Jowy Seah Yi; Chew, Wee Siong; Torta, Federico; Khoo, Chin Meng; Wenk, Markus R; Herr, Deron R; Tai, E Shyong; van Dam, Rob M
Abstract: Objectives: Sphingolipid concentrations have been associated with risk of type 2 diabetes and cardiovascular diseases. Because sphingolipids can be synthesized de novo from saturated fatty acids (SFA), dietary fatty acids may affect plasma sphingolipid concentrations. We aimed to evaluate dietary fat and protein intakes in relation to circulating sphingolipid levels. Methods: We used cross-sectional data from 2860 ethnic Chinese Singaporeans collected from 2004–2007. Nutrient intakes were estimated on the basis of a validated 159-item food frequency questionnaire. We quantified 79 molecularly distinct sphingolipids in a large-scale lipidomic evaluation from plasma samples. Results: Higher saturated fat intake was associated with higher concentrations of 16:1; O2 sphingolipids including ceramides, monohexosylcermides, dihexosylceramides, sphingomyelins, and sphingosine 1-phosphates. Higher polyunsaturated fat intake was associated with lower plasma long-chain ceramides and long-chain monohexosylcermide concentrations. Protein intake was inversely associated with concentrations of most subclasses of sphingolipids, with the exception of sphingolipids containing a 16:1; O2 sphingoid base. Lower intake of saturated fat and higher intake of polyunsaturated fat and protein may decrease plasma concentrations of several sphingolipid classes. Conclusions: These findings may represent a novel biological mechanism for the impact of nutrient intakes on cardio-metabolic health. Funding Sources: This work was supported by the National Research Foundation Investigatorship grant (NRF-NRFI2015–05, to MRW), A * STAR (I1901E0040), and the National University Health System (NUHSRO/2014/085/AF-Partner/01, DRH). FT was supported by the NRF and A * STAR IAF-ICP I1901E0040.